Approach to the Subject “DETE I EKOLOGIJA” by Applyingict at Preschool Institution - Hilčenko, Slavoljub; Nikolić, Sanja (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2022)
This text represents working approach to the subject “CHILD AND ECOLOGY” = „DETE I EKOLOGIJA” by applying ICT at preschool institution. The work is reflected in a combination of discussions about ecology, practical presentation of rules in recycling and sorting of various waste, projection of the educational film “EKOLOGIJA” and individual solving of play sheets by children. Among the others, the aim of the work was to determine attitudes of the educators (on the rating scale) about the presented approach to the work.